Effects of recreational cannabis on testicular function in primary infertile men. (5th August 2022) - Belladelli, Federico; Fallara, Giuseppe; Pozzi, Edoardo; Corsini, Christian; Cilio, Simone; Raffo, Massimiliano; d'Arma, Alessia; Boeri, Luca; Capogrosso, Paolo; Eisenberg, Michael; Montorsi, Francesco; Salonia, Andrea
Abstract: Background: Male factor contributes to up to 50% of cases of couples experiencing infertility. Cannabis is one of the most commonly used recreational drugs, and its effects on the reproductive system have been largely debated in the literature. Objectives: The aim of this study is to evaluate the effect of recreational cannabis use on total T (tT) levels, gonadal status, and sperm parameters in a cohort of primary infertile non‐Finnish, white‐European men. Materials and methods: Data of 2074 white‐European men visited for primary couple's infertility were analyzed. Lifestyle factors and cannabis use were investigated in all participants. Semen analyses were based on the 2010 World Health Organization reference criteria. Serum hormones were evaluated, and patients were subdivided based on their gonadal status. Health‐significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Descriptive statistics and linear regression analyses were used to test the association between cannabis use, sperm parameters, and hormonal levels. Logistic regression analyses tested potential predictors for abnormal sperm parameters and gonadal status. Results: Of 2074, 225 (10.9%) patients reported cannabis use in their lifetime. Total Testosterone levels were lower in cannabis users compared to nonusers ( p = 0.03). In a multivariable linear regression analysis, cannabis use was inversely associated with tT levels (ß = −0.372 ng/ml; p = 0.005) but not with follicle‐stimulating hormone nor with luteinizing hormone levels. Conversely, at multivariable logistic regression model cannabis use was not associated with the type of hypogonadism. At multivariable linear regression analysis, cannabis use was inversely associated with sperm morphology ( p = 0.007), while not with both sperm concentration and sperm motility. Similarly, at adjusted logistic regression analysis cannabis use resulted associated with teratozoospermia ( p = 0.039) but not with oligo‐, astheno‐, and azoospermia. Conclusions: Infertile men using cannabis are at higher risk of having lower testosterone levels and altered sperm morphology as compared with nonusers.